TEOLOGI AESTETIK MENURUT ST. BONAVENTURA DAN RELEVANSINYA BAGI KONSTRUKSI TEOLOGI KONTEKSTUAL DI INDONESIA - Kristoforus Bala, SVD, M.A. (Litbang STFT Widya Sasana Malang, 2015)
St. Bonaventure was one of the great medieval theologians who constructed his theology by employing not only philosophical and biblical ideas but also aesthetics. To him, the most holy triune God is the very source of all beauty. Divine beauty gushes forth from the very center of Trinity like a river. God the Father is the source of all beauty, the Son is called “Ars Patris” who reflects the Father’s beauty and the Holy Spirit is divine Beauty that renews, recreates and replenishes humanity, church and the whole world. In another words, humanity, church as the body of Christ and the whole created realities embody and reflect God’s magnificent beauty. All sacraments, in a very special way, mediate God’s power and beauty to the whole mystical body of Christ. They are visible signs established by God to renew, beautify and save God’s children. The most holy triune God is both the Origin and the End of all beauty. God will restore, renew and beautify humanity the church, and the whole world at the end of time. Bonaventure’s aesthetic theology is relevant to our context and his unique way of doing theology inspires us in our endeavor to construct a contextual theology in Indonesia.